The relationship between documentation quality and patient satisfaction in nursing care: Review - Alruqaie, Reef Ibrahim Mohammed; Albalawi, Basim Menwer; Almuqati, Lahiq Falhan S; Alsulami, Ahmad Nafal Mohmmed; Alyamani, Abdullah Mohammed Abdullah; Alamri, Badr Jaza; Alharbi, Majed Ayidh; Albather, Mohammed Hassan; Raea, Salem Mohammad; Alotaibi, Adil Mubarak F; Alahmadi, Fahad Salem; Alhrbi, Khaleel Ahmad (International journal of health sciences, 2021)
Background: Missed nursing care, encompassing delayed, incomplete, or omitted care, has emerged as a critical area of focus in the past decade due to its implications on patient outcomes and nursing satisfaction. It is influenced by factors like resource scarcity, teamwork, and patient acuity and has been linked to adverse events, particularly in vulnerable populations like older adults. Methods: This review synthesizes findings from seven systematic reviews exploring the frequency, predictors, and outcomes of missed nursing care across diverse hospital environments. Databases including EMBASE, Cochrane Library, CINAHL, and Scopus were searched, examining factors such as staffing levels, workload, and communication. Studies were primarily cross-sectional and observational. Results: Missed nursing care is prevalent globally, with significant variance influenced by staffing, workload, and communication dynamics. Commonly missed aspects include psychosocial support, communication, and patient education. Associations were found between missed care and adverse outcomes, such as infections, pressure injuries, and increased mortality, particularly in older patients. However, causality remains unclear due to methodological limitations. Conclusion: Missed nursing care is a multifaceted issue with broad implications for patient safety, nursing satisfaction, and healthcare outcomes. Further research, including longitudinal and experimental studies, is needed to elucidate causal pathways and develop effective interventions.